Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Judge Robert Coyle, Fresno County Young Lawyers Association President John McGregor, Leonard Herr shaking hands with Justice Stanley Mosk